Literature Review: The Relationship between Merdeka Curriculum and Student Learning Achievement - Kuntoro Aji; Asep Suherman; Febi Kurniawan; Irfan Zinat Achmad (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2023)
After the inauguration of Nadiem Makarim on October 23, 2019 as Indonesia's Minister of Education, Culture, Research and Technology, there were several excellent policies and programs made related to education in Indonesia. One of the superior products is the Merdeka Belajar Curriculum. This research is a literature review that examines and studies literature related to the Merdeka Curriculum on Student Learning Achievement. Data collection using the Preferred Reporting Items for Systematic Reviews and Meta Analysis (PRISMA) method. The curriculum that is currently being implemented is the Merdeka Curriculum, a curriculum with the aim of being able to facilitate the transition process of the national curriculum and to restore education that was previously less than optimal due to the Covid-19 pandemic, this Merdeka Curriculum in its application in order to optimize and provide opportunities for students to explore their interests and talents. A fun curriculum and learning system makes students feel comfortable during the process so that it can improve student achievement. Thus, there is a relationship between the Merdeka Curriculum and Student Learning Achievement.